Puas Sesuai Syari’at: Kepuasan Pernikahan pada Pasangan yang Menikah dengan Cara Ta’aruf - Muhammad Zein Permana; Asfahani Kurnia (Jurnal Psikologi Islam dan Budaya, 2021)
This study aims to explore marital satisfaction in couples who are married through ta'aruf. The method used is qualitative approach with phenomenological analysis. Data collection was carried out through in-depth interviews on 5 participants. This study describes that couples who marry through ta'aruf, have relatively the same object of satisfaction, namely religiosity with the aim of getting the rida and blessing of Allah Swt. This finding shows that research related to marital satisfaction, especially in couples who are married in a ta'aruf way, is no longer a subjective study, but has an alternative to begin to be objectively explained, predicted, and even controlled through religiosity factors. Also, marriage through ta'aruf is not only explained in the relational area between husband and wife, but also becomes part of the spiritual area and even religion, getting married as part of worship.